Electrochemical deposition of tin-copper alloy coatings - D. Y. Gulpa; I. I. Kuzmar; L. K. Kushner; N. V. Dezhkunov; A. A. Khmyl (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Solderable tin-base alloy coatings are widely used when assembling electronic products. The reorientation of production to lead-free technologies sets the task of developing new technological processes for the formation of coatings for electrical contacts with stable electrical properties, high soldering ability, which lasts for a long time. The features of the process of electrodeposition of coatings with a tin-copper alloy were experimentally investigated and the regularities of the influence of the electrolyte composition, current density, and ultrasound intensity on the cathode current efficiency of the alloy, the deposition rate, elemental composition, structure and functional properties of the precipitation were established. For sonochemical treatment an experimental setup developed at Research Laboratory 5.2 of BSUIR, which makes it possible to vary the intensity of ultrasonic vibrations in the range of 0.058– 1.7 W/cm2 , was used. It has been established that the use of ultrasound changes the formation mechanism of the electrochemical alloy, reduces cathodic polarization, increases the value of the limiting current and makes it possible to control the composition and structure of the precipitates. With an increase in the intensity from 0.12 to 0.95 W/cm2  the amount of copper in the coating increases by 4.5 times. The spreading coefficient of the solder is 92.59–98.44 %.